Area of spherical lune formed by two random planes - Pantelidis, Lysandros (My University, 2012)
An analytical solution for the exact calculation of the area of spherical lune formed by two random planes intersected in the sphere is given.
Keywords: Spherical lune; Surface area; Analytical solution; Random planes